2018
DOI: 10.1016/j.ijheh.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of future socio-economic and climate change scenarios on river microbial water quality

Abstract: Microbial surface water quality is important, as it is related to health risk when the population is exposed through drinking, recreation or consumption of irrigated vegetables. The microbial surface water quality is expected to change with socio-economic development and climate change. This study explores the combined impacts of future socio-economic and climate change scenarios on microbial water quality using a coupled hydrodynamic and water quality model (MIKE21FM-ECOLab). The model was applied to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Studies have shown that the extent of climate change impacts largely depend on assumptions made about socio-economic conditions [35,70,71]. Others have argued that applying different socio-economic scenarios is more effective than applying different climate change scenarios [72][73][74]. In this context, the global research community has developed Shared Socio-economic Pathways (SSPs), which provide a flexible framework for local scenario development, with quantitative and qualitative descriptions, that can be used in adaptation and vulnerability studies.…”
Section: Future Scenariosmentioning
confidence: 99%
“…Studies have shown that the extent of climate change impacts largely depend on assumptions made about socio-economic conditions [35,70,71]. Others have argued that applying different socio-economic scenarios is more effective than applying different climate change scenarios [72][73][74]. In this context, the global research community has developed Shared Socio-economic Pathways (SSPs), which provide a flexible framework for local scenario development, with quantitative and qualitative descriptions, that can be used in adaptation and vulnerability studies.…”
Section: Future Scenariosmentioning
confidence: 99%
“…The implications of climate-associated changes for microbial water quality in general, and FIB-pathogen relationships in particular, are profound, as these parameters have a dominant influence on the fate of waterborne pathogens and FIB (Patz et al 2008). Thus, the pressures generated by human population growth and global climate change have strong potential to accelerate issues of microbial pathogens in the beach sand water continuum in the 21 st century (Islam et al 2018).…”
Section: Overviewmentioning
confidence: 99%
“…Like global N models, global pathogen models rely on a common modeling design [ 40 43 ], are coarse-grained (0.5 by 0.5 degree), do not account for inputs from non-sewered populations, and do not map surface water flows to coastal ecosystems. Furthermore, while case studies can provide context for specific details–such as how fecal indicator bacteria respond to environmental conditions [ 44 ], the effect of future climate change and socioeconomic conditions [ 45 ] and continental-scale sensitivity and uncertainty analysis [ 46 ] global pathogen wastewater studies report results at national or larger scales. This crucially constrains our ability to assess the magnitude and distribution of coastal nutrient and pathogen stressors and develop regional and local policy recommendations and actions, much less compare fine-grained pathogen impacts to nutrient impacts on coastal communities and ecosystems.…”
Section: Introductionmentioning
confidence: 99%